What Next from London ? - Adams, Alexander; Atherton, Peggy; Baldwin, Wilhelmina; Grottick, Chris; Hodgson, Paul; Irani, Zara; Knall, Ulli; Lucie-Smith, Edward; Mosscrop, Max; Stevenson, Rebecca; Summers, John; Wagstaff, Lee; et al. (Oostende : Orion Art Gallery, 2001)
Adams, Alexander ; Atherton, Peggy ; Baldwin, Wilhelmina ; Brown, Jemima ; Brown, Dolly ; de Cadenet, Alexander ; Grottick, Chris ; Hodgson, Paul ; Irani, Zara ; Knall, Ulli ; Mosscrop, Max ; Stevenson, Rebecca ; Summers, John ; Wagstaff, Lee
biog. tent., prijzen, ... per kunstenaar
Nederlands & Frans & Engels
What Next from London ?, Orion Art Gallery, Oostende, 21.04.01 - 15.07.01
boek
Keywords: Groot-Brittannië; London